2014
DOI: 10.3390/toxins6082348
|View full text |Cite
|
Sign up to set email alerts
|

Is Increased Susceptibility to Balkan Endemic Nephropathy in Carriers of Common GSTA1 (*A/*B) Polymorphism Linked with the Catalytic Role of GSTA1 in Ochratoxin A Biotransformation? Serbian Case Control Study and In Silico Analysis

Abstract: Although recent data suggest aristolochic acid as a putative cause of Balkan endemic nephropathy (BEN), evidence also exists in favor of ochratoxin A (OTA) exposure as risk factor for the disease. The potential role of xenobiotic metabolizing enzymes, such as the glutathione transferases (GSTs), in OTA biotransformation is based on OTA glutathione adducts (OTHQ-SG and OTB-SG) in blood and urine of BEN patients. We aimed to analyze the association between common GSTA1, GSTM1, GSTT1, and GSTP1 polymorphisms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 44 publications
(48 reference statements)
0
21
2
1
Order By: Relevance
“…Indeed, our group has showed that GSTT1-active genotype is associated with TCC risk in men exposed to pesticides . Regarding the potential role of GSTT1 in metabolism of OTA and aristolochic acid, the results of our recent investigation did not show involvement of this enzyme in OTA metabolism (Reljic et al 2014), while data on aristolochic-acid metabolism and GSTT1 are lacking. Still, it is noteworthy mentioning that our results on association of GSTT1 polymorphism between risk of TCC bladder cancer and residence in BEN-area are in line with results of Lebrun et al (2006) who pointed out the role of GSTT1 polymorphism in the extent of DNA damage induced by OTA.…”
Section: Smoking Habitscontrasting
confidence: 59%
See 4 more Smart Citations
“…Indeed, our group has showed that GSTT1-active genotype is associated with TCC risk in men exposed to pesticides . Regarding the potential role of GSTT1 in metabolism of OTA and aristolochic acid, the results of our recent investigation did not show involvement of this enzyme in OTA metabolism (Reljic et al 2014), while data on aristolochic-acid metabolism and GSTT1 are lacking. Still, it is noteworthy mentioning that our results on association of GSTT1 polymorphism between risk of TCC bladder cancer and residence in BEN-area are in line with results of Lebrun et al (2006) who pointed out the role of GSTT1 polymorphism in the extent of DNA damage induced by OTA.…”
Section: Smoking Habitscontrasting
confidence: 59%
“…Recently, our group showed that individuals with one or both low-activity GSTA1*B alleles are at 1.6-fold higher risk of BEN than individuals carrying the wild type homozygous GSTA1*A/*A genotype (Reljic et al 2014). The main result obtained from this study pointed out that TCC risk in individuals from BEN areas is modified by GSTA1 gene polymorphism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations